The Significance of Perceived Ease of Use and Usefulness on Purchase Intention. An Adaptation from the Technology Acceptance Model (TAM) with the Moderation Role of Trust at Tiket.com in Indonesia - Rachel Ghea Kelose Tarigan; Efin Shu (Universitas Pelita Harapan, 2025)
The rapid growth of online travel agencies (OTAs) and the increasing reliance on digital platforms for travel bookings have significantly transformed consumer behavior in the travel industry. Despite the growth of OTAs, Tiket.com has faced problems like system errors and difficult website navigation that made customers hesitate to make purchases. By adapting the Technology Acceptance Model (TAM), this research investigates the moderating role of trust between perceived ease of use, perceived usefulness, and purchase intention at Tiket.com. A quantitative approach was employed, with the data collected using a convenience sampling technique. The sample consisted of 110 respondents, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that perceived usefulness significantly and positively influences purchase intention, with a path coefficient of 0.507 and a p-value of 0.000. Conversely, perceived ease of use did not influence purchase intention, with a path coefficient of 0.067 and a p-value of 0.250. Additionally, the moderation of trust was found to be insignificant among these relationships. Tiket.com is suggested to focus on improving its perceived usefulness by increasing users' empowerment in selecting travel options, improving the user experience, providing enhanced customization features, and easy-to-use comparison tools.